Language policy and identity politics in the United States - Schmidt, Ronald, 1943- (Philadelphia : Temple University Press, 2000)
An engaging discussion about the use of English and other languages in the United States.
Acknowledgments; Introduction: A Politics of Language in the United States?; I. The Issues and the Context; II. The Arguments; III. Critique and Reform; Notes; References; Index.
Includes bibliographical references (pages 257-274) and index.
Print version record.
English.
JSTOR
Keywords: Language policy -- United States; Americanization; Cultural pluralism -- United States; Politique linguistique -- États-Unis.; Américanisation.; Diversité culturelle -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Sociolinguistics; SOCIAL SCIENCE -- General; Americanization; Cultural pluralism; Language policy; United States; Mehrsprachigkeit; Sprachpolitik; USA; Amerikanisches Englisch